A positive association between a polymorphism in the HTR2B gene and cocaine-crack in a French Afro-Caribbean population. (25th November 2020) - Lacoste, Jerome; Lamy, Sandrine; Ramoz, Nicolas; Ballon, Nicolas; Jehel, Louis; Maroteaux, Luc; Thibaut, Florence
Abstract: Objectives: Cocaine dependence has a strong heritability component. The aim of this study was to investigate the putative association between the serotonin 2B receptor gene ( HTR2B ), crack use disorders and impulsivity. Methods: A French Afro-Caribbean male population of patients with crack use disorders ( n = 80) was compared to healthy Afro-Caribbean male controls ( n = 60). Comorbid ADHD and impulsivity were assessed. Five single nucleotide polymorphisms (SNPs) in the HTR2B gene were selected: rs643700, rs6736017, rs1549339, rs17586428 and rs3806545. These SNPs were chosen to include most of the linkage disequilibrium blocks in the HTR2B gene. The French translation of the Barratt Impulsivity Scale BIS-11 was used to evaluate impulsivity. Comorbid ADHD was diagnosed using the Wender Utah Rating Scale-25 item for Attention Deficit-Hyperactivity Disorder. Results: We have observed a positive association between the rs6736017 polymorphism and crack use disorders in a French Afro-Caribbean male population. Conclusions: In our population, the risk effect of HTR2B rs6736017 appeared to be specific to individuals with crack use disorders rather than being driven by impulsivity or ADHD alone.